Hubungan Dukungan Keluarga dan Peran Tenaga Kesehatan dengan Pemanfataan Prolanis pada Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Helvetia - Savira Medinah Nasution; Siti Khadijah Nasution; Zulfendri Zulfendri (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The number of people with diabetes mellitus in the Helvetia Health Center work area is 2,883 people and the number of prolanis participants who have diabetes mellitus is only 45 people or 10 percent.  The prolanis achievement target is 75 percent and based on this, it can be seen that the prolanis capaain is very far from the achievement target. The purpose of this study is to analyze the relationship between family support and the role of health workers with the use of prolanis in patients with diabetes mellitus at the Helvetia Health Center. The type of research used is survey research with a Cross Sectional design. The population in this study is 2,883 people with diabetes mellitus at the Helvetia Health Center. The number of samples in the study was 100 people with the slovin formula The sampling technique was carried out by simple random sampling. Diabetic mellitus patients who are ≥ 40 years old are 86 people (86.0%), women are 55 people (55.0%), diabetic mellitus patients who have an income Medan City MSEs are 78 people (78.0%) and diabetic mellitus patients who are still working as many as 61 people (61.0%) and 39 people (39.0%) are not working. The results of statistical analysis using the chi-square test showed that there was a relationship between family support and the use of Prolanis in the Helvetia Health Center (p=0.007) and there was no relationship between the role of health workers and the use of Prolanis in the Helvetia Health Center (p=0.143). There is a relationship between family support and the use of prolanis in patients with diabetes mellitus at the Helvetia Health Center and there is no relationship between the role of health workers and the use of prolanis in patients with diabetes mellitus at the Helvetia Health Center. Keywords: Diabetes, Prolanis, Utilization  ABSTRAK Jumlah penderita diabetes melitus di wilayah kerja Puskesmas Helvetia sebanyak 2.883 orang dan jumlah peserta prolanis yang diabetes melitus hanya sebanyak 45 orang atau 10 persen.  Target capaian prolanis sebesar 75 persen dan berdasarkan hal tersebut dapat dilihat bahwa capaain prolanis sangat jauh dari target capaian. Tujuan dalam penelitian ini adalah untuk menganalisis hubungan dukungan keluarga dan peran tenaga kesehatan dengan pemanfataan prolanis pada penderita diabetes melitus di Puskesmas Helvetia. Jenis penelitian yang digunakan adalah penelitian survei dengan desain Cross Sectional. Populasi pada penelitian ini adalah pasien diabetes melitus di Puskesmas Helvetia yaitu 2.883 orang. Jumlah sampel dalam penelitian adalah 100 orang dengan rumus slovin Teknik pengambilan sampel dilakukan dengan cara simple random sampling.  Penderita diabetes melitus yang berumur ≥ 40 tahun sebanyak 86 orang (86,0%), perempuan sebanyak 55 orang (55,0%) penderita diabetes melitus yang memiliki pendapatan UMK Kota Medan sebanyak 78 orang (78,0%) dan penderita diabetes melitus yang masih bekerja sebanyak 61 orang (61,0%) dan tidak bekerja sebanyak 39 orang (39,0%). Hasil analisis statistik dengan menggunakan uji chi-square diperoleh ada hubungan antara dukungan keluarga dengan pemanfaatan Prolanis di Puskesmas Helvetia (p=0,007) dan tidak ada hubungan peran tenaga kesehatan dengan pemanfaatan Prolanis di Puskesmas Helvetia (p=0,143). Ada hubungan dukungan keluarga dengan pemanfaatan prolanis pada penderita diabetes melitus di Puskesmas Helvetia dan tidak ada hubungan peran tenaga kesehatan dengan pemanfaatan prolanis pada penderita diabetes melitus di Puskesmas Helvetia. Kata Kunci: Diabetes, Prolanis, Pemanfaatan